Teacher Training: reflections of mathematical education in higher education - Barbara Lutaif Bianchini; Gabriel Loureiro de Lima; Eloiza Gomes (Universidade Federal do Rio Grande do Sul, 2019)
This paper maps the productions of the Mathematics Teachers Training generated by the Working Group on Mathematical Education in Higher Education, of the Brazilian Society of Mathematical Education. This investigation is aimed to analyze, among other aspects, the initial training of Mathematics teachers, the role of supervised internship practice and the development of the teaching professional. We sought to highlight the concerns that researchers, whose main field of interest is teaching in Higher Education, have about the initial and continued training of Mathematics teachers. We have identified, by means of Content Analysis, six pillars in which the topics presented in the body of the analysis are concentrated.